Institutional environment and access to microfinance by self-employed women in the rural areas of Edo state, Nigeria - Okojie, Christiana; Monye-Emina, A.; Eghafona, K.; Osaghae, G.; Ehiakhamen, J. O. (International Food Policy Research Institute, 2009)
The major objective of this study was to examine the relationship between the institutional environment of microfinance and access of rural women to microfinance. Focus group sessions were held with groups of rural women who are clients of formal and informal Microfinance Institutions (MFIs) in Esan Local Government Area of Edo State, Nigeria. The two formal institutions were the Ekpoma branch of Lift Above Poverty Organization Microfinance Bank and the Ujoelen Microfinance Bank. Fifteen case studies with fourteen women and one man were also examined. They had all accessed loans from formal and/or informal MFIs. Main findings Institutional environment: The traditional informal microfinance institutions still exist side by side with the formal MFIs. These informal mechanisms have not been absorbed into the regulated microfinance sector. They are still very popular with rural women, many of whom have belonged to these “meetings” for over a decade. These informal thrift and credit societies still remain the only source of funds available to poor women who have not been able to access the formal sector microfinance institutions. Why are rural women poor? According to respondents, rural women in the study area are poor because of heavy family responsibilities. They have to feed their family when the husband does not provide because they cannot leave their children hungry. Additionally, they pay their children’s school fees as they do not want their children to be driven out of school. As a result of all these factors, women do not have enough capital for their trading and farming activities and cannot save. The women are hardworking and if they have capital they can trade with it and lift themselves out of poverty. The respondents gave examples of successful business women in the area that succeeded because they had access to credit from LAPO and other sources. Why it is difficult for women to borrow from banks? Rural women in particular find it difficult to borrow from banks because most do not have bank accounts, they have no collateral to present to the bank, and many women do not know the procedures for accessing bank loans. As they explained, while men inherit land and other property which they can use as collateral, women do not inherit property. They also said that women need their husband’s consent to borrow money from the bank. Sources of microfinance for rural women: The main source of finance for the majority of rural women is their contribution from their savings/market association. However, with the advent of microfinance banks, more rural women are now accessing formal microfinance institutions. Rural women have accessed loans from the Lift Above Poverty Organization (LAPO) and Ujoelen Microfinance Banks. One of the women’s groups also accessed credit from a government agency – the National Poverty Eradication Programme (NAPEP). Some of the more successful women have accessed multiple sources of credit over the years as their businesses have expanded. None of the participants has accessed loans from any of the commercial banks which have established microfinance banks/departments operating in the study area. Impact of microfinance on women’s businesses and lives: According to the women interviewed, microcredit has had positive impacts on their businesses and family life. Many of them have been able to expand their businesses. In some cases, they no longer have to buy goods on credit thereby avoiding interest payments and increasing their profits. At the family level, unlike in the past, they can make more contributions to their family upkeep, they eat better food, are able to pay children’s fees regularly and with less stress. A few who were so inclined have joined political parties such as the PDP and AC. However, to properly assess the impact of microfinance, a quantitative study using measures of impacts will be more reliable. Government policy and access to microfinance in rural areas of Edo State: In the study area, government policy has helped to bring formal microcredit sources to women on a larger scale. The Community Banks that transformed into MFBs now target women as microfinance client, which they did not do when they operated as Community Banks. Microcredit is also available to women through the LAPO, which has always targeted women’s groups. However, while the formal institutions have transformed into Microfinance Banks as required by the government’s Microfinance Policy, the traditional savings institutions still remain outside the regulated microfinance sector. Recommendations: From our findings, we would like to recommend and emphasize the following: * Informal microfinance institutions should be registered at the local government level and encouraged to keep good records in order to provide data on the volume of informal sector transactions in microfinance. * Women find it difficult to access formal finance institutions for several reasons, including lack of collateral or bank accounts and the belief that women do not repay loans. * More MFBs should be established in all Local Government Areas (LGAs) in order to reach the rural dwellers, especially women who should be targets of MFB operations. * Commercial banks which have established microfinance departments should develop products that target rural self-employed women. * MFBs should be properly supervised to protect depositors’ funds. The experiences of depositors with failed Community Banks should not be repeated. Access to microfinance can help rural self-employed women to expand their businesses and improve their personal and family well-being. Women will be encouraged to open bank accounts if they are assured that their deposits are safe and that they will be able to access loans for their businesses at reasonable terms such as low interest rates and convenient savings and repayment schedules.